SECTION OF ALL-RUSSIAN SCIENTIFIC SOCIETY OF CARDIOLOGISTS ON RATIONAL PHARMACOTHERAPY IN CARDIOLOGY (Рациональная фармакотерапия в кардиологии)
Section of All-Russian Scientific Society of Cardiologists on Rational Pharmacotherapy in Cardiology.